PENGARUH EFIKASI DIRI, LOCUS OF CONTROL, DAN DUKUNGAN SOSIAL KELUARGA TERHADAP KEMATANGAN KARIR MAHASISWA JURUSAN MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS RIAU ANGKATAN 2019-2020 - ,Raden Lestari Garnasih, Gilang Ramadhan Purba , Marnis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of Self Efficasy, Locus Of Control, and Family Social Support on the Career Matury majoring in management, Faculty of Economics and Business, Riau University, Class 2019-2020. The population in this study included active student of the Department of Management, Faculty of Economics and business, Riau University, class 2019-2020, totaling 581 Students. Primary data were collected using a quetionnare as an instrument to prove the result of the study, to test the hypothesis in this study using multiple regression analysis with the help of the SPSS program. The sampling technique for this study used the Slovin method (581 Students as the population and 85 student as the sample). The result showed that: 1) there was a Positive and significant influence of Self Efficasy on the Career Matury of Management student of the Faculty of Economics & Business, Riau University, 2) there was a positive and significant influence of Locus Of Control on the Career Matury of Management students of the faculty of Economics & business, Riau University, 3) there was a positive and significant influence of Family Social Support on the Career Matury of Management student of the Faculty of Economics & Business, Riau University, 4) there is a Simultaneous significant influence between Self Efficasy, Locus Of Control, and Family Sosial Support on the Career Matury of Management student at the Faculty of Economics & Business, Riau University. Keyword : Self Efficasy, Locus Of Control, Family Social Support, and Career Matury